Discrimination of Breast Cancer by Measuring Prostate-Specific Antigen Levels in Women's Serum - Chang, Ying-Feng; Hung, Shuo-Hui; Lee, Yi-Jang; Chen, Ran-Chou; Su, Li-Chen; Lai, Chao-Sung; Chou, Chien (Analytical chemistry (Washington), 2011)
Prostate-specific antigen (PSA) has been reported to be a potential biomarker of breast cancer. Serum PSA of normal women is around 1 pg/mL, which is usually undetectable by current assay methods; thus an ultrasensitive measurement of PSA expression in women's serum is necessary to distinguish normal from malignant breast diseases. To enhance the sensitivity of conventional immunoassay technology for the detection of PSA in sera, we adopted a localized surface plasmon coupled fluorescence fiber-optic biosensor, which combines a sandwich immunoassay with the localized surface plasmon technique. The concentration of total PSA (t-PSA) (from 0.1 to 1000 pg/mL) in phosphate-buffered saline solution and the normalized fluorescence signal exhibit a linear relationship where the correlation coefficient is 0.9574. In addition, the concentration of additional t-PSA in 10-fold-diluted healthly women's serum across a similar range was measured. The correlation coefficient for this measurement is 0.9142. In clinical serum samples, moreover, the experimental results of t-PSA detection show that both the mean value and median of normalized fluorescence signals in the breast cancer group (155.2 and 145.7, respectively) are higher than those in the noncancer group (46.6 and 37.1, respectively). We also examined the receiver operating characteristic curve for t-PSA, and the area under the curve (AUC) is estimated to be 0.9063, the AUC being used to measure the performance of a test to correctly identify diseased and nondiseased subjects.